Keracunan Parasetamol Pada Kucing Dan Anjing: Gejala Klinis dan Terapi: Paracetamol Poisoning in Cats and Dogs: Clinical Symptoms and Therapy - Yanuartono Yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Slamet Raharjo; Hary Purnamaningsih; Nurman Haribowo (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Acetaminophen, commonly known as paracetamol, is a non-steroidal anti-inflammatory drug commonly used in human medicine for its antipyretic and analgesic action. As paracetamol became readily available in many over-the-counter and no-prescription products, reports of paracetamol poisoning in dogs and cats became more common. The toxicity of paracetamol is more pronounced in cats when compared to dogs. Clinical signs of paracetamol toxicity include depression, weakness, tachypnea, dyspnea, vomiting, hypothermia, facial or paw edema, hepatic necrosis, and death. The characteristics of severe paracetamol poisoning are methemoglobinemia, cyanosis, anemia, and jaundice. Although there are no specific antidotes, acetylcysteine is the drug of choice for paracetamol poisoning treatment. Symptomatic and supportive therapies play a more definitive role in the management of paracetamol poisoning. This paper aims to briefly review the clinical symptoms, diagnosis, and treatment of paracetamol poisoning in dogs and cats.